2018
DOI: 10.1097/md.0000000000013690
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mineralocorticoid receptor antagonists in postmyocardial infarction patients with or without left ventricular dysfunction

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…40 RAASi TherapydBenefits and Hyperkalemia Risk Renin-angiotensin-aldosterone system inhibitors are recommended for patients with hypertension, 42 HF, 43,44 stable coronary artery disease, 45 CKD, diabetic kidney disease (DKD), 46 and diabetes. 47,48 They improve survival in patients with CKD, 49 HF, 50,51 and post-MI status 52 and also provide kidney benefits in patients with non-DKD 53 and DKD. 54,55 Many patients who would otherwise benefit from RAASis either do not receive FIGURE 1.…”
Section: Risk Factorsmentioning
confidence: 99%
“…40 RAASi TherapydBenefits and Hyperkalemia Risk Renin-angiotensin-aldosterone system inhibitors are recommended for patients with hypertension, 42 HF, 43,44 stable coronary artery disease, 45 CKD, diabetic kidney disease (DKD), 46 and diabetes. 47,48 They improve survival in patients with CKD, 49 HF, 50,51 and post-MI status 52 and also provide kidney benefits in patients with non-DKD 53 and DKD. 54,55 Many patients who would otherwise benefit from RAASis either do not receive FIGURE 1.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Although these drugs may reduce symptoms, it has been reported the difficulty to improve cardiovascular outcomes by using diuretics. 29,30 It has been showed that the treatment with mineral corticoid receptor antagonists decreased all cause-mortality and cardiovascular death in post-MI patients with left ventricular dysfunction, whereas did not exhibit any cardiovascular benefit in those without left ventricular dysfunction. 31 Recently, diuretics use (furosemide was the one most frequently administered) 32 has been considered the strongest clinical predictor of cardiovascular events in patients with HF, and in those with a previous MI and impaired glucose tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…Diuretics represent a widespread pharmacological treatment in patients with concomitant hypertension or HF. Although these drugs may reduce symptoms, it has been reported the difficulty to improve cardiovascular outcomes by using diuretics 29,30 . It has been showed that the treatment with mineral corticoid receptor antagonists decreased all cause‐mortality and cardiovascular death in post‐MI patients with left ventricular dysfunction, whereas did not exhibit any cardiovascular benefit in those without left ventricular dysfunction 31 .…”
Section: Discussionmentioning
confidence: 99%
“… 8 MRA has also been shown to be beneficial for patients with a reduced EF in the postmyocardial infarction setting. 43 MRA should be discontinued in patients in whom serum potassium cannot be maintained less than 5.5 mEq/L and should not be used in women with serum creatinine above 2.0 mg/dL and in men with creatinine above 2.5 mg/dL 8 because of the excess risk of hyperkalemia.…”
Section: Heart Failure With Reduced Ejection Fractionmentioning
confidence: 99%